MANNOPROTEIN PRODUCTION FROM CANDIDA APICOLA IN THE FORMULATED BEAN SPROUT EXTRACT MEDIA - Latifah FAUZIAH; Roostita Lobo BALIA; Jajang GUMILAR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The five-year research devoted to the study of harvesting methods and desiccation effects on the yields and quality of oil seed flax of dual use was conducted in the field conditions on the dark-chestnut soil in the South of Ukraine during 2013-2017. The study defined the highest effectiveness of pre-harvesting desiccation of the crop by glufosinate ammonium in the dose 2 L ha-1 followed by direct harvesting that can increase the yield of flax seeds by 0.15 t ha-1 or by 11.9%, and the yield of flax straw – by 0.22 t ha-1 or by 12.7%. At the same time, the increase in the yield is accompanied by the improvement of qualitative parameters of the straw through better orientation of the stems in a roll, the share of fibres, which are longer than 200 mm, in comparison with the separate harvesting increases by 8%, and the contamination of the straw decreases 3 times in comparison to the variant without desiccation. Desiccation conducted by using glyphosate preparation in the dose 3 L ha-1 allowed increasing of the net profit by 15.67 euro ha-1.